PARTISISPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN POHUWATO - Muslimah Muslimah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Public participation in the formation of local regulation is critical in determining the success of the development process in inonesia. Because community participation is a prerequisite in determining the success of the development process in Indonesia The successful implementation of development is inseparable from the active participation of community members in a region or city, either as part of the social system as well as the individual who is a very important part of the system of regional governance, because in principle the implementation of development in the area proposed to build a prosperous society and spiritual material in the area. The successful implementation of the development is inseparable from the active participation of community members in a region or city, either as part of the social system as well as the individual who is a very important part of the system of local government, because in principle the implementation of development in the area proposed to build a prosperous society and material spiritual in that area.